HUBUNGAN ANTARA INTERNAL LOCUS OF CONTROL DAN PENGALAMAN PRAKTIK KERJA INDUSTRI DENGAN KEMATANGAN KARIER PADA SISWA PROGRAM STUDI KEAHLIAN TEKNIK KOMPUTER DAN INFORMATIKA - Ni Putu Mita Puspita Dewi; Luh Putu Eka Damayanthi; Dessy Seri Wahyuni; I Made Gede Sunarya (KARMAPATI (Kumpulan Artikel Mahasiswa Pendidikan Teknik Informatika), 2014)
This study aimed to determine therelationship between internal locus of control towardcareer maturity, the relationship between practiceindustrial work experience toward career maturity, italso the relationship between internal locus of controland practice industrial work experience toward careermaturity, that is student career maturity Skills Programin Computer Enginering and Information Technologyat SMK in Buleleng regency academic year 2013/2014.This type of research is a correlation study that isexpost-facto which consists of two independentvariables that is internal locus of control (X1) andpractice industrial work experience (X2), it also onedependent variable that is career maturity (Y). Thepopulation in this study were 531 people and the samplewere 175 respondents. Data for X1, X2, and Y werecollected through questionnaires. The collected datawere analyzed using parametric statistical prerequisitetest of homogeneity, normality, linearity, andmulticollinearity.The result of this research showed that there wasa positive and significant relationship between internallocus of control toward career maturity which wasshown by the contribution of 36,053%. Practiceindustrial work experience has a positive andsignificant relationship toward career maturity whichwas shown by the contribution of 51,107%. Internallocus of control and practice industrial work experiencehas a positive and significant relationship toward careermaturity which was shown by the contribution of53,217%.